La questione della liceità della circoncisione “rituale” tra tutela dell’identità religiosa del gruppo e salvaguardia del diritto individuale alla integrità fisica (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Notazioni introduttive - 2. La circoncisione “terapeutica” e quella “profilattica” - 3. La circoncisione “tradizionale” e quella (propriamente) “rituale” - 4. L’orientamento che giudica la pratica contraria ai diritti fondamentali del minore - 5. La circoncisione rituale ebraica e la legge 8 marzo 1989, n. 101 - 6. La circoncisione rituale tra libertà religiosa, diritto alla salute e diritto all’integrità fisica - 7. Osservazioni conclusive.The issue of lawfulness of “ritual” circumcision: protection of collective religious identity versus violation of individual’s right to physical integrityABSTRACT: The present essay deals with the issue regarding the lawfulness of male “ritual” circumcision, that is performed for non-therapeutic reasons. Female genital mutilation (FGM) is considered as a violation of human rights in the Western world; on the contrary, male circumcision for non-therapeutic reasons is currently tolerated. However, in many Countries experts hightlighted the permanent effect of circumcision on bodily integrity and the special importance of the right to self-determination. The Author stresses problems that the circumcision poses in the Italian legal system, considering special legislation related to Jewis (law No. 101/1989) and case law that assesses the practice lawful in case it is performed with the parents’ consent and according to the rules of medical art.